Proximate and oragnoleptic analysis of carrot-fortified and vanilla flavoured cakes (2023)
This study investigated the proximate and organoleptic properties of carrot-fortified and vanilla flavoured cake. Specifically, it determined: proximate composition of carrot-fortified and vanilla flavoured cake: and organoleptic properties of carrot-fortified and vanilla flavoured cake. Samples of the products were prepared using standard methods. The product was divided into two parts, one part was subjected to proximate analysis while the other part was subjected to sensor}' evaluation. Proximate analysis of carrot- fortified and vanilla flavoured cake was carried out using standard methods. Twenty panellists were involved in the sensory evaluation of the products. A 7-point hedonic scale was used to collect data on the organoleptic properties of the samples. Dahl for sensory evaluation were analysed using percentages (%). Result of proximate analysis showed that carrot-fortified cake had the highest content of protein (15.6%). Moisture Content (15.6%)), ash (2.4%). crude fibre (I.2%), Tannins (55mg/100g), Saponins (35mg/100g) 35, Ascorbic Acid (14.5mg/100g), Carotenoids (350µg/100g), Thiamine (0.21mg/100)g), Riboflavin (0.17mg/100g), Niacin (2.65mg/100g) and lowest content of fat (25.0%), carbohydrate (42.2%) when compared to vanilla-flavoured cake. Also, the organoleptic result showed that carrot-fortified cake was ranked higher and accepted by the panellists when compared to vanilla flavoured cake based on the 7-point hedonic scale rating. Rased on these findings it was recommended that: further research could be carried out on the shelf life of carrot cake and mode of preservation with the use of natural preservatives such as vinegar and physiochemical analysis of the cakes during different stages of storage.